2022
DOI: 10.1200/jco.2022.40.16_suppl.3561
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib (REGO) plus FOLFIRINOX as frontline treatment in patients (pts) with RAS-mutated metastatic colorectal cancer (mCRC): A phase I/II, dose-escalation and dose-expansion study.

Abstract: 3561 Background: Standard treatment options for RAS-mutated mCRC pts include the combination of bevacizumab with FOLFIRINOX, a three-drug chemotherapy regimen. Unlike bevacizumab, REGO – an oral multi-tyrosine kinase agent - exhibits not only antiangiogenic properties with cytostatic effects but also true cytotoxic effects. We report the preliminary results of the FOLFIRINOX-R trial (NCT03828799), in which we evaluated the safety and the efficacy of REGO in combination with FOLFIRINOX in pts with RAS-mutated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, Adenis et al (18) reported a study with full-dose FOLFIRINOX (5-FU, Folinic acid, irinotecan, oxaloplatin) plus full-dose regorafenib (160mg/day, days 4-10) can be safely delivered, those 13 patients have reported an overall response rate of 62% (95% CI 32%-86%) and median PFS was 9.1 months (range: 3.1; 15.4).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Adenis et al (18) reported a study with full-dose FOLFIRINOX (5-FU, Folinic acid, irinotecan, oxaloplatin) plus full-dose regorafenib (160mg/day, days 4-10) can be safely delivered, those 13 patients have reported an overall response rate of 62% (95% CI 32%-86%) and median PFS was 9.1 months (range: 3.1; 15.4).…”
Section: Introductionmentioning
confidence: 99%